2021
DOI: 10.1111/ppc.12788
|View full text |Cite
|
Sign up to set email alerts
|

The determination of intercultural sensitivity and ethnocentrism levels among nurses and nursing students: A border of city, Turkey

Abstract: Aim The current study is a descriptive‐comparative study and aims to determine intercultural sensitivity and ethnocentrism levels among nurses and nursing students. Method The study was conducted with 207 nurses working at a State Hospital and 211 nursing students studying at a University between November 30, 2019, and January 20, 2020. The data were collected using a descriptive characteristics form, the Intercultural Sensitivity Scale, and the Ethnocentrism Scale. Findings It was found that both nurses and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…The participants' mean total score on the intercultural sensitivity scale was 89.34 ± 10.01. This finding was similar to the findings obtained in the literature both in Turkey and other countries (Aksoy & Akkoç, 2020;Aslan & Kizir, 2019;Chang et al, 2013;Kargın & Çapar Çiftçi, 2020;Karasu et al, 2022;Kürtüncü et al, 2018;Toda & Maru, 2018;Yilmaz et al, 2017Yilmaz et al, , 2019. This finding was also important in terms of demonstrating that the nurses had a culturally empathetic understanding.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The participants' mean total score on the intercultural sensitivity scale was 89.34 ± 10.01. This finding was similar to the findings obtained in the literature both in Turkey and other countries (Aksoy & Akkoç, 2020;Aslan & Kizir, 2019;Chang et al, 2013;Kargın & Çapar Çiftçi, 2020;Karasu et al, 2022;Kürtüncü et al, 2018;Toda & Maru, 2018;Yilmaz et al, 2017Yilmaz et al, , 2019. This finding was also important in terms of demonstrating that the nurses had a culturally empathetic understanding.…”
Section: Discussionsupporting
confidence: 91%
“…The reason for this situation may be associated with the nurses' experiences of difficulties in using interaction language and skills when encountering individuals with different cultural characteristics and statuses. In a similar study carried out by Karasu et al (2022), the mean score of nurses in the subscale of interaction engagement was found to be higher. It is thought that this finding was associated with nurses who were enthusiastic about gaining cultural knowledge and skills by receiving education in the clinical field.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In the literature, several studies have been conducted to investigate the relationship between intercultural sensitivity and the level of ethnocentrism in different disciplines (Akyıl & Yıldırım, 2020; Bilgiç & Şahin, 2019; Çimen, 2019; Demir & Kiran, 2016; Erdogan & Okumuslar, 2020; Karasu et al, 2021; Kaya et al, 2021; Leung et al, 2020; Tezcan, 2020). In many studies conducted in the field of nursing, a negative relationship has been reported between the levels of intercultural sensitivity and ethnocentrism.…”
Section: Introductionmentioning
confidence: 99%